Early Detection of Lung Cancer Using DNA Promoter Hypermethylation in Plasma and Sputum - Hulbert, Alicia; Jusue-Torres, Ignacio; Stark, Alejandro; Chen, Chen; Rodgers, Kristen; Lee, Beverly; Griffin, Candace; Yang, Andrew; Huang, Peng; Wrangle, John; Belinsky, Steven A.; Wang, Tza-Huei; et al. (Clinical cancer research, 2017)
Purpose: CT screening can reduce death from lung cancer. We sought to improve the diagnostic accuracy of lung cancer screening using ultrasensitive methods and a lung cancer–specific gene panel to detect DNA methylation in sputum and plasma. Experimental Design: This is a case–control study of subjects with suspicious nodules on CT imaging. Plasma and sputum were obtained preoperatively. Cases (n = 150) had pathologic confirmation of node-negative (stages I and IIA) non–small cell lung cancer. Controls (n = 60) had non-cancer diagnoses. We detected promoter methylation using quantitative methylation-specific real-time PCR and methylation-on-beads for cancer-specific genes (SOX17, TAC1, HOXA7, CDO1, HOXA9, and ZFP42). Results: DNA methylation was detected in plasma and sputum more frequently in people with cancer compared with controls (P < 0.001) for five of six genes. The sensitivity and specificity for lung cancer diagnosis using the best individual genes was 63% to 86% and 75% to 92% in sputum, respectively, and 65% to 76% and 74% to 84% in plasma, respectively. A three-gene combination of the best individual genes has sensitivity and specificity of 98% and 71% using sputum and 93% and 62% using plasma. Area under the receiver operating curve for this panel was 0.89 [95% confidence interval (CI), 0.80–0.98] in sputum and 0.77 (95% CI, 0.68–0.86) in plasma. Independent blinded random forest prediction models combining gene methylation with clinical information correctly predicted lung cancer in 91% of subjects using sputum detection and 85% of subjects using plasma detection. Conclusions: High diagnostic accuracy for early-stage lung cancer can be obtained using methylated promoter detection in sputum or plasma. Clin Cancer Res; 23(8); 1998–2005. ©2016 AACR.